2020
DOI: 10.3390/ijerph17176193
|View full text |Cite
|
Sign up to set email alerts
|

Sport Promotion through Sport Mega-Events. An Analysis for Types of Olympic Sports in London 2012

Abstract: A substantial amount of attention has been devoted towards the potential sport legacy of the Olympic Games. In spite of the increasing academic interest in this topic, there is a knowledge gap as far as sport legacy is concerned by types of different sports. The authors bridge this gap by analysing the evolution of 43 different Olympic/Paralympic sport modalities in the two-year period after the London 2012 Olympics. By using data from the Active People Survey with a sample of 165,000 people annually, and cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 39 publications
3
16
0
Order By: Relevance
“…An increase of 700,000 people participating in sport or PA once per week was observed in England after the London 2012 OG. 40,42,43 But, as pointed out by Milton et al, 42 the proportion of the population participating in sport or PA once per week remained stable (36.6% in 2007/2008, 36.9% in 2011/2012, and 36.1% in 2015-2016), because the total population of England also increased. Therefore, it is essential to consider the relative proportion of the active population rather than the absolute number.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…An increase of 700,000 people participating in sport or PA once per week was observed in England after the London 2012 OG. 40,42,43 But, as pointed out by Milton et al, 42 the proportion of the population participating in sport or PA once per week remained stable (36.6% in 2007/2008, 36.9% in 2011/2012, and 36.1% in 2015-2016), because the total population of England also increased. Therefore, it is essential to consider the relative proportion of the active population rather than the absolute number.…”
Section: Discussionmentioning
confidence: 96%
“…Six studies observed an increase in PA/sport practice after hosting elite sport events. 40,43,55,59,63,64 Null or mixed lagged effects were observed in 3 42,55,59 and 7 [34][35][36]44,48,49,60 studies, respectively; 3 studies observed a lagged increase in PA/sport participation after hosting elite sport events. 40,43,47 One study, which did not provide the age range of the studied population, observed a null effect of hosting elite sport events on sport memberships.…”
Section: Effect Of Hosting Elite Sport Events On Pa/sport Practice In...mentioning
confidence: 99%
See 1 more Smart Citation
“…Government policy on reinvestment of net broadcasting revenue in grassroots sports and equitable distribution of funding away from elite leagues and into the lower tiers and the grassroots would all help support sport participation. An increase in participation, particularly with new participants who have the tendency to purchase more sports consumables, would lead to higher consumption of sporting goods and services and thus to greater budgetary surpluses [50].…”
Section: Reinvesting Sport Related Budgetary Surplusesmentioning
confidence: 99%
“…Supporting sports participation could be improved by government policy by reinvesting net broadcasting revenues in grassroots sports and by distributing funding from elite leagues to lower tiers. A higher number of participants, especially new ones who are more likely to purchase sports consumables, leads to a higher demand for sporting goods and services, leading to greater budgetary surpluses (Kokolakakis and Lera-Lopez 2020).…”
mentioning
confidence: 99%